Negotiating the practical ethics of 'self-tracking' in intimate relationships: Looking for care in healthy living. (December 2020) - Will, Catherine M.; Henwood, Flis; Weiner, Kate; Williams, Rosalind
Abstract: In this paper, we offer insights into practices of tracking as part of healthy living through talk about home blood pressure and weight from adults living in the UK. Drawing on theoretical resources from feminist ethics of care and Science and Technology Studies on care as socio-material practice, we build on interest in the relational dimensions of tracking and the potential for intimate surveillance and care using monitoring technologies. Our cases offer not only new perspectives in a field that has often focused on fitness tracking but also help go beyond a narrow focus on surveillance, showing how surveillance and care may be intertwined in the everyday negotiation of health-related tracking and other 'health practices' in family life. Using the diversity in our relatively large sample, and reflecting on the different types of interview completed, we highlight the varied ways in which adults engage with tracking blood pressure and weight (or body mass index) in the context of established relationships. The combination of attentiveness and appeals to responsibility for maintaining health as something owed to a partner can make tracking a very ethically sensitive area. In this paper we emphasise that reciprocity is one important way in which couples make tracking feel more like care. Tracking together or discussing it can take couples in this direction even if the actual practice remains somewhat difficult. On the other hand, responsiveness to someone else's feelings, including a desire to avoid the topic altogether, or avoid weight as a specific parameter, might all help move towards more caring tracking. We therefore develop a more sustained account of care in relation to tracking than in previous work, and a novel account of tracking as a (potential) care practice between adult partners. Highlights: Explores tracking of blood pressure and BMI in the context of 'healthy living'. Combines insights from feminist ethics of care and STS 'care-in-practice'. Analyses 'tracking-as-care' negotiated in intimate adult relationships. Negotiations understood as practical ethics - disentangling care and surveillance. Shows how method of joint interviews surface such negotiations.